Body Shaming, Beauty Pressures and Yoruba Popular Music: Implications for Adolescents’ Mental Health and Well-being in Nigeria - Adekola , Olaolu Emmanuel; Olowokere, Yinka Wilson (African Journal of Stability and Development (AJSD), 2025)
Body shaming, an act of abusing or shaming the body of a person, is often evident in how people interact with one another, and it is expressed in their art, especially music. What constitutes body shaming differs significantly across age groups and generations. Existing studies on the phenomenon of body shaming have paid little or no attention to the dynamism of body shaming and its perceived effects in relation to Yoruba popular music in Nigeria. This study therefore investigated the dynamics of body shaming as exemplified in selected Yoruba popular music with a view to examining what constitutes body shaming and its effects on youths’ and adolescents’ mental health well-being. The study adopted ethnographic research design with qualitative approach, using In-depth interviews and key informant interviews to elicit responses from respondents. Music tracks– “Pxy Drip” by Naira Marley and “Omo pupa” by Victor Olaiya– also constituted the data. Data were content analysed. The findings revealed that some texts of popular music constitute one of the channels through which body shaming is promoted. There is a generational divide in the perception of body shaming, with younger audiences demonstrating heightened sensitivity to body-related lyrics. Resultant effects of body shaming, especially in contemporary times include harmful body enhancement, depression, low self-esteem, and anxiety, among others. The paper argues that repeated exposure to lyrics of contemporary popular music that promote body shaming can contribute to self-consciousness and internalised beauty pressures, which can trigger mental health disorders among adolescents. It is, therefore, imperative for stakeholders to censor the contents of music that are being released for public consumption because of the negative effects such music may have on youths.